If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -20 = 35x Reorder the terms: -20 + 15x = 35x Solving -20 + 15x = 35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35x' to each side of the equation. -20 + 15x + -35x = 35x + -35x Combine like terms: 15x + -35x = -20x -20 + -20x = 35x + -35x Combine like terms: 35x + -35x = 0 -20 + -20x = 0 Add '20' to each side of the equation. -20 + 20 + -20x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -20x = 0 + 20 -20x = 0 + 20 Combine like terms: 0 + 20 = 20 -20x = 20 Divide each side by '-20'. x = -1 Simplifying x = -1
| 3(4x+3(x-2))=24 | | 7x-56x= | | 2X-4=0.5X+8 | | 7y+70= | | 3(x-4)=-21 | | x^2=-65 | | 2(6+2x)=8x | | 2a+3b+2c=32 | | 6x+2y=1 | | 2m-8=8 | | z^2+17z+52= | | 6x-5-3x=14+3 | | 3x-7=5+2x | | 2x-12=24 | | -2y-6=-8 | | -3a-12=3 | | 4x+13=-57-10x | | 5-5n=-20 | | -32-2x=13-7x | | 434443+0= | | 43444333+665564644= | | X^2+8x+84=0 | | 3(x-8)=5(-2x+11) | | 5x^2-12x+15=0 | | -5x+11=7x-19 | | (23x-23)-2=23 | | 2x^2-10x+12=0 | | 2x-4=34x | | 7x-2x=20 | | 6.4=4x | | 2x^2-x=4 | | 9v(8v^3)=0 |